2019
DOI: 10.1186/s13031-019-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to family and organized violence and associated mental health in north Korean refugee youth compared to south Korean youth

Abstract: Background: Studies on populations affected by organized violence have shown elevated levels of family violence against children. This form of violence has been found to contribute to children's psychopathology independently of traumatic experiences related to war, persecution or flight. Little is known, so far, about the exposure to family violence and its relation to mental health in North Korean refugee youth affected by political violence. The aim of this study was to examine the amount of organized and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Considering the considerable stigma surrounding mental illness and the low health literacy of NKDs residing in South Korea, it is necessary to provide community-based information to vulnerable groups to promote knowledge of mental illness and ensure the safe use of medications. [20,22,37] • Repatriation experiences [38] • Long staying periods after entrance [21,22,44] • Perceived discrimination [10] • Low income [13,46,47] • Family relationships (family violence, family cohesion) [17,48,49] • Physical illnesses [19,51] • Alexithymia [31] • Emotion regulation strategy [40] • Thoughts of personal failure [41] • Resilience [42]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the considerable stigma surrounding mental illness and the low health literacy of NKDs residing in South Korea, it is necessary to provide community-based information to vulnerable groups to promote knowledge of mental illness and ensure the safe use of medications. [20,22,37] • Repatriation experiences [38] • Long staying periods after entrance [21,22,44] • Perceived discrimination [10] • Low income [13,46,47] • Family relationships (family violence, family cohesion) [17,48,49] • Physical illnesses [19,51] • Alexithymia [31] • Emotion regulation strategy [40] • Thoughts of personal failure [41] • Resilience [42]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevalence of various forms of family violence in their lifetime, compared with young SKNs, young NKDs had significantly higher rates of neglect (25.8% vs. 6.2%) and physical abuse (32.3% vs. 10.8%), whereas psychological abuse did not vary between these two groups. The authors observed that the severity of depressive symptoms and PTSD in young NKDs was associated with the number of family violence and traumatic events, but not with higher levels of organized violence [17]. These findings suggest that abusive experiences by family members are strongly linked to the psychopathology of NKD adolescents in the context of organized violence.…”
Section: Family Relationshipsmentioning
confidence: 90%
See 3 more Smart Citations